PATIENT EMERGENCY AND DOCTOR ALERT SYSTEM - MS.BIRAJDARLAXMI; MS.BOGA SONIKA; MS.KANDGULE SHRADDHA (International Journal of Innovations in Engineering Research and Technology, 2021)
The primary function of this system is to monitor a patient in emergency. We have to providethe device to patient from sending alerts to doctors. The message sent to the Microcontroller. The Microcontroller then transmits the data to the user in the form of SMS. Here we are using the GSM modem in order to transmit the information. From the transmitter, the parameters are sent as an SMS to the care taker or the expert or a doctor which have been given as the recipient. Not only we send the information through GSM module as SMS, we also display the readings on LCD. We also provide Android app for same.